2009
DOI: 10.1080/19315260802508283
|View full text |Cite
|
Sign up to set email alerts
|

Control of Bacterial Wilt Disease of Tomato Through Integrated Crop Management Strategies

Abstract: Tomato cultivation is severely affected by bacterial wilt disease caused by the soilborne pathogen Ralstonia solanacearum (previously known as Pseudomonas solanacearum Smith). Effects of rotation of tomato (Lycopersicon esculentum Mill.) with other crops on soil populations of R. solanacearum and on bacterial wilt disease incidence of tomato were evaluated in the field. Monocropped Cassava (Manihot esculenta Crantz), Mucuna puriens L., Crotalaria juncea L., and intercrops of Cassava/Crotalaria, Cassava/Mucuna,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Taiwo et al (2007) reported a total loss of tomato crop from combined infestation of bacterial and fungal pathogens on farmers' fields in Nigeria. Prevalence of bacterial wilt of tomato leading to a loss of about 80% in south-western Nigeria was reported by Adebayo et al (2009). Ralstonia solanacearum (Smith) Yabuuchi et al (syn.…”
Section: Impact Of Soil Amendments and Weather Factors On Bacterial Wmentioning
confidence: 86%
“…Taiwo et al (2007) reported a total loss of tomato crop from combined infestation of bacterial and fungal pathogens on farmers' fields in Nigeria. Prevalence of bacterial wilt of tomato leading to a loss of about 80% in south-western Nigeria was reported by Adebayo et al (2009). Ralstonia solanacearum (Smith) Yabuuchi et al (syn.…”
Section: Impact Of Soil Amendments and Weather Factors On Bacterial Wmentioning
confidence: 86%
“…Management of BW of tomatoes is difficult, and growers frequently rely on integrated pest management tactics such as crop rotation, cultural practices, fumigation, host resistance, and grafting with disease-resistant rootstocks [ 13 , 14 , 15 , 16 , 17 , 18 ]. Even so, control is frequently inadequate or too expensive.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that strains of R. solanacearum can be altered based on soil type, its texture, pH and moisture content [16]. During heavy rainfall on infested soil, water runoff contaminates rivers which are the sources of irrigation water [17].…”
Section: Introductionmentioning
confidence: 99%